The Communion of Saints and Prayer - Boris Paschke (Богословські роздуми: Східноєвропейський журнал богословʼя, 2022)
This article studies the Christian Church as a communion of saints by focusing on the New Testament references to prayer. Because of their content, some prayers are directly and expressly concerned with the communion and unity of Christian believers. But independent of their specific topic or request, all prayers provide worthwhile insights with regard to the communion of saints. The importance (and even necessity) of Christians praying together as well as interceding and giving thanks for each other is stressed. Numerous prayers having been uttered by individual believers in solitude are later reported in letters in order to strengthen the rest of the Church. By taking into account the unfortunate physical fragmentation of churches during the Covid-19 pandemic, the contribution highlights what the Church today, as a physical (and digital) communion of saints, can learn from the New Testament’s teaching on prayer.